Effect of authentic leadership on employee creativity in project-based organizations with the mediating roles of work engagement and psychological empowerment - Fozia Mubarak; Ayesha Noor (Cogent Business & Management, 2018)
The purpose of this research is to explore the relationship that exist between authentic leadership and employee creativity in project-based organizations. The mediating effects of work engagement and psychological empowerment on the relationship of authentic leadership and employee creativity were also focused in this research. Proficient organizations ensure presence of systematic practical approaches that can benefit employees in increasing their engagement levels and making them feel more empowered. The data were collected through convenience sampling from 246 respondents of different Project-based NGO's of Islamabad and Rawalpindi. The findings suggest that employee creativity is significantly associated with authentic leadership, work engagement, and psychological empowerment. In addition, it was also revealed that extra engaged employees at work were more creative and sense of empowerment also mediates the relationship between authentic leadership and employee creativity. This research contributes to the current literature that authentic leadership relates to employee creativity, through mediating effects of work engagement and psychological empowerment.
Keywords: 650